The unity of consciousness: subjects and objectivity - Schechter, Elizabeth (Philosophical studies, 2013)
This paper concerns the role that reference to subjects of experience can play in individuating streams of consciousness, and the relationship between the subjective and the objective structure of consciousness. A critique of Tim Bayne's recent book indicates certain crucial choices that works on the unity of consciousness must make. If one identifies the subject of experience with something whose consciousness is necessarily unified, then one cannot offer an account of the objective structure of consciousness. Alternatively, identifying the subject of experience with an animal means forgoing the conceptual connection between being a subject of experience and having a single phenomenal perspective.